Systems for Sustainability - Barreto, Cristiane Gomes (Sustainability in Debate, 2014)
Obra resenhada: Donella Meadows. Thinking in systems: a primer. Edited by Diana Wright. White River Junction, Vermont: Chelsea Green Publishing Company, 2008. 185 p. eBook Inclui figuras e bibliografia. ISBN: 978-160358148-6.